1999
DOI: 10.1074/jbc.274.33.23627
|View full text |Cite
|
Sign up to set email alerts
|

TRAIL Death Pathway Expression and Induction in Thyroid Follicular Cells

Abstract: To determine whether programmed cell death in thyroid follicular cells can be related to activation of the tumor necrosis factor-related apoptosis-inducing ligand (TRAIL) pathway, we examined the expression and function of this pathway in primary thyroid follicular cells and a papillary thyroid carcinoma cell line in vitro. Despite the expression of TRAIL receptors death receptor 4 and death receptor 5, purified TRAIL could not induce programmed cell death (PCD) in any of the thyroid follicular cells examined.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0
2

Year Published

1999
1999
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(53 citation statements)
references
References 47 publications
(49 reference statements)
2
49
0
2
Order By: Relevance
“…Presence of CHX (1 mg/ml) signi®cantly enhanced TRAIL-induced apoptosis in both NPA ( Figure 1B(h)) and SW579 cell lines as more than 80% of cells were killed after 8 h incubation with TRAIL (200 ng/ml) and 97% apoptosis after 24 h ( Figure 2). Under the same conditions, normal thyroid follicular cells could not be killed by TRAIL (Bretz et al, 1999, and data not shown). Signi®cant apoptotic changes were not noted when thyroid cancer cells (NPA and SW 579 in particular) were treated with either TNF-a or agonistic Fas Ab (CH11) alone.…”
Section: Apoptosis Of Thyroid Cancer Cellsmentioning
confidence: 65%
See 1 more Smart Citation
“…Presence of CHX (1 mg/ml) signi®cantly enhanced TRAIL-induced apoptosis in both NPA ( Figure 1B(h)) and SW579 cell lines as more than 80% of cells were killed after 8 h incubation with TRAIL (200 ng/ml) and 97% apoptosis after 24 h ( Figure 2). Under the same conditions, normal thyroid follicular cells could not be killed by TRAIL (Bretz et al, 1999, and data not shown). Signi®cant apoptotic changes were not noted when thyroid cancer cells (NPA and SW 579 in particular) were treated with either TNF-a or agonistic Fas Ab (CH11) alone.…”
Section: Apoptosis Of Thyroid Cancer Cellsmentioning
confidence: 65%
“…Little is known however, whether the apoptotic machinery of thyroid cancer cells triggered by death-inducing cytokines is operational and can be activated for tumoricidal purposes. Bretz et al (1999) studied the e ect of in¯ammatory cytokines interferon g, TNF-a and interleukin-1b on the expression of TRAIL in thyroid cancer cell line KAT5, however, the mechanism of apoptosis triggered by TRAIL was not worked out. Recently, it has been reported that protein kinase C e is able to induce apoptotic cell death of thyroid cells (Knauf et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Treatment with PI-PLC could remove the TRAIL-R3 receptors from the cell membrane [11,40]. As well, an inhibitor such as CHX suppressing protein synthesis might also influence the resistance of islet cells to the TRAIL death pathway [52]. Primary islet cells were found to be susceptible to apoptosis mediated by TRAIL, in the presence of the protein synthesis inhibitor CHX in this study.…”
Section: Discussionmentioning
confidence: 62%
“…However, not all transformed tumor cells are susceptible to the TRAIL death pathway [40,58]. The major factors that determine the susceptibility remain unclear [37,52]. There might be some unidentified changes not related to transformation leading to the susceptibility to TRAIL-mediated apoptosis in the primary beta cells.…”
Section: Discussionmentioning
confidence: 99%
“…Proinflammatory cytokines, such as TNF-α and IL1, can affect immunityrelated apoptosis. TNF-α and IL1 in combination with IFN-γ have been shown to induce apoptosis in thyroid cell culture studies [21][22][23] . The mechanism of apoptosis in HT seems to be associated with the stimulation of cytokines secreted from local lymphocytes 23 .…”
Section: Cumhuriyet Medical Journalmentioning
confidence: 99%